CALCULATION OF INCOME TAX (PPH) ARTICLE 21 PERMANENT EMPLOYEES (Case Study at the Semarang District Attorney's Office in 2020) - Afifah Nurul Khikmah; Sumanto Sumanto (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
Income Tax is a mandatory contribution imposed on a Tax Subject on income received or earned in one tax year. The problem that arises is that there is still an error in calculating the income tax at the Semarang District Attorney's Office. The purpose of this study was to determine the calculation, payment, and reporting of Income Tax (PPh) Article 21 for permanent employees at the Semarang District Attorney's Office in 2020 and to determine the suitability of calculating, paying, and reporting Income Tax (PPh) Article 21 for permanent employees at the Prosecutor's Office. State of Semarang Regency in 2020 based on Law Number 36 of 2008 and Regulation of the Director General of Taxes Number PER-16/PJ/2016. The data used are primary and secondary data. Methods of data collection using observation, interviews and literature study. The writing method uses descriptive and exposition methods. The results of this study indicate that the Semarang District Attorney's Office has calculated, paid and reported Income Tax (PPh) Article 21 for permanent employees in 2020 through a third party (KPPN). In tax calculations, there are still errors including in determining status, office fees, pension contributions and PTKP which affect the determination of Article 21 Income Tax (PPh) which is deducted, resulting in an underpayment difference of Rp.1,864,150.00